Avaliação da pressão de colapso de dutos submarinos com danos - Melo Netto, Caroline Ferraz de (2017)
The present work is related to collapse pressure and buckle propagation of dented pipelines installed in deep waters. Numerical models based on finite elements method and small-scale buckle propagation tests in dented samples were performed. These models and experimental tests have taken into account different pipeline and dent geometries. Material tests were performed to predict mechanical properties of the material of the samples tested. The numerical models were calibrated and a numericalexperimental correlation was obtained. A parametric study was developed using commercial pipeline geometries, aiming to study the influence of dent geometry and magnitude on the collapse pressures for dented pipelines with different wall thicknesses.Significant influence of magnitude and shape of dents in the collapse pressures was observed, both experimentally and numerically. For pipes with big dents, a new stable equilibrium trajectory was observed after the initial collapse - revealing a different behavior from what has being reported in the literature. Through the parametric study, it was possible to propose a simplified model to predict the collapse pressure of dented pipes, using the maximum ovalisation of damaged section, the ratio D/t and the collapse pressure of the intact pipe.